2015
DOI: 10.2515/therapie/2015013
|View full text |Cite
|
Sign up to set email alerts
|

Example of an Investigation of an “Emergent” Phenomenon in Addiction Vigilance: the Case of Methylphenidate

Abstract: -Abuse of and addiction to medication are a major public health issue which is evolving fast, in particular in countries like France, one of the largest consumers of medication in Europe. As a single source of information is not generally sufficient to measure a phenomenon as difficult to apprehend as medication-related addiction, as can be seen in the case of methylphenidate, it is essential to mobilise all the tools available, here surveillance programmes developed by the French CEIP Addiction vigilance netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
1
20
1
Order By: Relevance
“…This trend has already been described by different drug utilization studies in other European countries [6,7,9,28,29] . An extensive variability was observed in the European levels between 2002 and 2010, for example, +425% in Denmark (0.8-4.2 DDD/1,000 inhabitants/day), +67% in France (0.18-0.3 DDD/1,000 inhabitants/day), +116% in Germany (1-2.16 DDD/1,000 inhabitants/day), and +122% in the Netherlands (2.04-4.53 DDD/1,000 inhabitants/day) [28] . In our study, 2,802 patients were MPH users in 2011, leading to an exposure of 0.39 DDD/1,000 inhabitants/day.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This trend has already been described by different drug utilization studies in other European countries [6,7,9,28,29] . An extensive variability was observed in the European levels between 2002 and 2010, for example, +425% in Denmark (0.8-4.2 DDD/1,000 inhabitants/day), +67% in France (0.18-0.3 DDD/1,000 inhabitants/day), +116% in Germany (1-2.16 DDD/1,000 inhabitants/day), and +122% in the Netherlands (2.04-4.53 DDD/1,000 inhabitants/day) [28] . In our study, 2,802 patients were MPH users in 2011, leading to an exposure of 0.39 DDD/1,000 inhabitants/day.…”
Section: Discussionmentioning
confidence: 72%
“…In our study, 2,802 patients were MPH users in 2011, leading to an exposure of 0.39 DDD/1,000 inhabitants/day. The fact that such a situation of MPH abuse was observed in France, even though the level of exposure in the general population is 'low' in comparison to other European countries, is an important warning in terms of public health [28,29] . Currently, there are many drug utilization studies that describe the prevalence or incidence of ADHD drugs, patient profile and data on ADHD drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36] Using dependence-relatedness indicator on the whole database (including Europe and other countries), the authors showed that routine screening would have quantitatively highlighted a potential signal with pregabalin already in the second quarter. To the best of our knowledge, there are few examples of using VigiBase ™ for identification of safety signals related to abuse or addiction, with the exception of methylphenidate as discussed by Micallef et al [37] In Germany, pregabalin was ranked as the 12 th most sold drug in Germany in 2009, with an increase in prescriptions of approximately 22% in 2009 compared to 2008. Face to this indirect reference to a possible abuse of this drug, Gahr et al analysed all reported cases of pregabalin abuse and dependence in Germany that had been submitted to the responsible federal authority, the German Federal Institute for Drugs and Medical Devices (Bundesinstitut für Arzneimittel und Medizinprodukte [BfArM]).…”
Section: Why a Pharmacoepidemiological Approach Is Needed? Pregabalinmentioning
confidence: 99%
“…One example of this could be the misuse of methylphenidate, identified in the PACA-Corsica region: [27] the question of whether to reiterate this survey in other regions can be raised in case of a generalisation of the phenomenon.…”
Section: National Mobilisation Following a Regional Signalmentioning
confidence: 99%